Slowly expanding/evolving lesions as a magnetic resonance imaging marker of chronic active multiple sclerosis lesions - Elliott, Colm; Wolinsky, Jerry S; Hauser, Stephen L; Kappos, Ludwig; Barkhof, Frederik; Bernasconi, Corrado; Wei, Wei; Belachew, Shibeshih; Arnold, Douglas L (Multiple sclerosis, 2019)
Chronic lesion activity driven by smoldering inflammation is a pathological hallmark of progressive forms of multiple sclerosis (MS). To develop a method for automatic detection of slowly expanding/evolving lesions (SELs) on conventional brain magnetic resonance imaging (MRI) and characterize such SELs in primary progressive MS (PPMS) and relapsing MS (RMS) populations. We defined SELs as contiguous regions of existing T2 lesions showing local expansion assessed by the Jacobian determinant of the deformation between reference and follow-up scans. SEL candidates were assigned a heuristic score based on concentricity and constancy of change in T2- and T1-weighted MRIs. SELs were examined in 1334 RMS patients and 555 PPMS patients. Compared with RMS patients, PPMS patients had higher numbers of SELs ( = 0.002) and higher T2 volumes of SELs ( < 0.001). SELs were devoid of gadolinium enhancement. Compared with areas of T2 lesions not classified as SEL, SELs had significantly lower T1 intensity at baseline and larger decrease in T1 intensity over time. We suggest that SELs reflect chronic tissue loss in the absence of ongoing acute inflammation. SELs may represent a conventional brain MRI correlate of chronic active MS lesions and a candidate biomarker for smoldering inflammation in MS.